Pravastatin Chronic Treatment Sensitizes Hypercholesterolemic Mice Muscle to Mitochondrial Permeability Transition: Protection by Creatine or Coenzyme Q10 - Busanello, Estela N. B.; Marques, Ana C.; Lander, Noelia; de Oliveira, Diogo N.; Catharino, Rodrigo R.; Oliveira, Helena C. F.; Vercesi, Anibal E. (Frontiers in Pharmacology, 2017)
Statins are efficient cholesterol-lowering medicines utilized worldwide. However, 10% of patients suffer from adverse effects specially related to skeletal muscle function. Pro- or anti-oxidant effects of statins have been reported. Here we hypothesized that statins induce muscle mitochondrial oxidative stress leading to mitochondrial permeability transition (MPT) which may explain statin muscle toxicity. Thus, our aims were to investigate the effects of statin chronic treatment on muscle mitochondrial respiration rates, MPT and redox state indicators in the context of hypercholesterolemia. For this purpose, we studied muscle biopsies of the hypercholesterolemic LDL receptor knockout mice (LDLr-/-) treated with pravastatin during 3 months. Plantaris, but not soleus muscle of treated mice showed significant inhibition of respiration rates induced by ADP (-14%), oligomycin (-20%) or FCCP (-40%). Inhibitions of respiratory rates were sensitive to EGTA (Ca2+ chelator), cyclosporin A (MPT inhibitor), ruthenium red (inhibitor of mitochondria Ca2+ uptake) and coenzyme Q10 (antioxidant), indicating that pravastatin treatment favors Ca2+ induced MPT. Diet supplementation with creatine (antioxidant) also protected treated mice against pravastatin sensitization to Ca2+ induced MPT. Among several antioxidant enzymes analyzed, only catalase activity was increased by 30% in plantaris muscle of pravastatin treated mice. Oxidized lipids, but not proteins biomarkers were identified in treated LDLr-/- plantaris muscle. Taken together, the present results suggest that chronic pravastatin administration to a model of familial hypercholesterolemia promotes mitochondrial dysfunctions in plantaris muscle that can be counteracted by antioxidants administered either in vitro (CoQ10) or in vivo (creatine). Therefore, we propose that inhibition of muscle mitochondrial respiration by pravastatin leads to an oxidative stress that, in the presence of calcium, opens the permeability transition pore. This mitochondrial oxidative stress caused by statin treatment also signals for cellular antioxidant system responses such as catalase upregulation.